Modeling and Analysis of DC-Link Dynamics in DFIG System With an Indicator Function - Heng Nian; Yunyang Xu; Liang Chen; Maowei Zhu (IEEE Access, 2019)
The doubly fed induction generator (DFIG) is the most widely applied wind turbine in practice and contains a dc-link capacitance in its back-to-back converter to deliver the generated power and to provide dc-link voltage for converters. In small-signal analysis, fluctuations in dc-link voltage can be caused by perturbations injected at the ac-terminals of DFIG system and the dc-link voltage fluctuations can affect the outputs of ac-terminals in reverse. It has been found in former publications that this dc-link dynamic behavior is able to shape the small-signal characteristics of DFIG system and influence the system stability. However, the modeling and analysis for the dc-link dynamic behavior is lacked, which makes it difficult to indicate the influencing factors of dc-link dynamics and how to suppress the negative influence of weakly-damped dc-link dynamics on the DFIG system. In this paper, the mechanism of dc-link dynamics and how dc-link dynamics affect the small-signal characteristics of DFIG system are described at first. Then, an indicator function that models the dc-link dynamic behavior is firstly defined and then obtained based on harmonic linearization method. The proposed indicator function will be applied to describe the impedance shaping effect of dc-link dynamics on DFIG system, indicate the influencing factors of dc-link dynamics and analyze the influence of weakly-damped dc-link dynamic behavior. Several experiments based on Control-hardware-in-loop (CHIL) platform will also be carried out to verify the analytical models and theoretical analysis in this paper.